Nanoscopy of Aluminum Plasmonic Cavities by Cathodoluminescence and Second Harmonic Generation. Issue 11 (2nd August 2022) - Zar, Tchiya; Ron, Racheli; Shavit, Omer; Krause, Alon; Gachet, David; Salomon, Adi
Abstract : Herein, centrosymmetric aluminum plasmonic structures composed of triangular cavities are studied and their long‐range coupling by cathodoluminescence nanoscopy are visualized. Four different plasmonic structures containing the same subunit are studied. The plasmonic modes of the individual triangular subunits are localized at the triangle sides rather than at the vertices, in agreement with other studies. Yet, upon strong interaction between the cavities, a redistribution of the electromagnetic field is observed such that it delocalizes around the cavities in the form of a contour, providing a mode enhancement and a pronounced nonlinear response as observed by second harmonic generation. Comparison between plasmonic structures made of either silver or aluminum reveals that the metal dielectric function plays an important role in the interaction between the cavities. This work provides a rationale for designing plasmonic structures with enhanced nonlinear activity. Abstract : By using cathodoluminescence, it is demonstrated that upon strong interaction between aluminum plasmonic cavities, the electromagnetic field undergoes delocalization around the cavities and a ring contour is formed, in analogy to a benzene ring. Following that a pronounced SHG response is observed, revealing the potential of those coupled aluminum plasmonic structures for nonlinear optics.